Food-dependent exercise-induced anaphylaxis following intake of nuts - Manappallil, Robin George; Anand, Thushara (Asian Journal of Medical Sciences, 2020)
Allergic reactions can be mild or life threatening. Food-dependent exercise-induced anaphylaxis (FDEIA) is a severe form of allergic reaction in which symptoms develop only after exercising within a few hours of eating a specific food. The condition is, at times, underdiagnosed. Proper history taking is essential, especially when patients present with allergic reactions after exertion and food intake. The patient being described developed FDEIA because of exercising after eating nuts.